DESAIN DAN KONSTRUKSI RUMPON NELAYAN PELABUHAN PERIKANAN SAMUDERA KENDARI STUDI KASUS KMN. BUKIT SAFA - Made Mahendra Jaya; Iya Purnama Sari; Yulia Estmirar Tanjov; Wulandari Sarasati; Komang Krisna Kusuma Putera (Universitas Mataram, 2026)
Fish aggregating devices (FADs) have various designs and constructions depending on the area where they are used. This study aims to observe the design and construction of FADs used by fishermen at the Kendari Fishing Port. The method used in this research is a case study. The FAD observed is the one used by fishermen on the vessel KMN. Bukit Safa. The data collected includes the size and components of the FAD. The collected data were analyzed using descriptive analysis. The design and construction of the raft light fishing aid used on KMN. Bukit Safa consists of a wooden frame, Styrofoam, lamps, batteries, and a power inverter. The design and construction of the FAD consist of components such as weights, ropes, floats, attractors, and a lamp housing. The rope used for the FAD is called tali mandar, which is made from a mixture of PA and PE rope materials with a diameter of 24 mm. A total of 30 rolls of rope were used, equivalent to approximately 2400 m. The FAD floats are made from Styrofoam measuring 100 cm x 100 cm x 60 cm. The FAD weights are made of concrete, which is a mixture of cement and sand, weighing around 100 kg. The weights used are cube-shaped with dimensions of 60 cm x 60 cm x 60 cm.